Exploring Light Harvesting in Blends of Cesium Lead Halide Nanocrystals with Fullerene Derivatives - Charalambous, Eleftheria; Papagiorgis, Paris G.; Polycarpou, Nefeli; Galatopoulos, Fedros; Ioakeimidis, Apostolos; Choulis, Stelios A.; Christodoulou, Sotirios; Itskos, Grigorios (My University, 2024)
Light harvesting devices based on metal halide perovskite nanocrystals (NCs) rely on the application of ligand washing or ligand exchange processes to transform pristine, glassy NC solids into electronically active NC arrays. A less explored route combines such treatments with the fabrication of NC heterojunctions with organic semiconductors to promote charge transfer through conductive pathways within the blends. Herein, optical spectroscopy and photoconductivity is implemented for a detailed investigation of the charge generation and charge extraction process in blends of green CsPbBr3 NCs or red CsPb(Br,I)3 NCs capped with short octylamine/octanoic-acid ligands with the fullerene derivative phenyl-C70-butyric acid methyl ester (PC70BM). Incorporation of the fullerene results in efficient quenching of the NC photoluminescence (PL) and the emergence of a fast subnanosecond decay channel in the transient PL, which is consistent with efficient interfacial dissociation of the NC excitons via electron transfer to the PC70BM. Importantly, the photocurrent in lateral devices with gold contacts is improved by up to 2 orders of magnitude upon fullerene incorporation, with optimum concentration of 20% per weight PC70BM for both green and red absorbing NCs. Short, post synthetic thermal annealing up to 100 °C further improves charge extraction due to better material blending and film quality, increasing by an additional order of magnitude the photo response of the devices.
Keywords: Perovskite solar cells; Blending; Bromine compounds; Charge transfer; Conversion efficiency; Extraction; Fullerenes; Heterojunctions; Image enhancement; Lead compounds; Ligands; Metal halides; Nanocrystals; Perovskite